Cumplimiento de los indicadores de calidad en el servicio de Emergencia del HGMYM - Loja, periodo Marzo - Julio 2022 - Celi Iñiguez, Byron Antonio (2023)
Compliance with patient safety practices reflects the quality of care granted by the health service and increases when care is provided substantiated by the best scientific, professional, and institutional conditions. Therefore, daily nursing acting revolves around excellence during the execution of the professional practice, which is why manuals and protocols of care are incorporated that allow the health professional to standardize criteria to make the best decision. For this reason, the present research was proposed which had as its objective evaluating the fulfillment of quality indicators in the Emergency Department of the General Hospital Manuel Ygnacio Monteros. For this purpose, observational, descriptive, and cross-sectional research was carried out, using an observation list as an instrument for data collection, which was created from the formats and checklists established in the MSP patientuser safety manual. With regard to results, it was obtained that the Emergency service had 23 nurse professionals, 7 auxiliaries, and 3 inmates; it is distributed in 3 areas and has 13 beds. In terms of the application of administrative practices, a percentage of 92.07% was reached, where the lowest scored practice was correct patient identification; the practices that obtained the highest performance were the assistance practices (94.39%) with minimal deficiencies in the control of concentrated electrolytes and prevention of pressure ulcers, while the practices with the lowest performance were the administrative/assistance practices (88.08%), where hand hygiene presented 40% non-compliance. In conclusion, the emergency department does not reach the optimal standard of compliance in the application of safe practices